2004
DOI: 10.1074/jbc.m405442200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Geranylgeranylation Mediates the Effects of 3-Hydroxy-3-methylglutaryl (HMG)-CoA Reductase Inhibitors on Microglia

Abstract: Inflammatory responses involving microglia, the resident macrophages of the brain, are thought to contribute importantly to the progression of Alzheimer's disease (AD) and possibly other neurodegenerative disorders. The present study tested whether the mevalonate-isoprenoid biosynthesis pathway, which affects inflammation in many types of tissues, tonically regulates microglial activation. This question takes on added significance given the potential use of statins, drugs that block the rate-limiting step (3-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 65 publications
2
39
0
1
Order By: Relevance
“…In addition, recent prospective studies have demonstrated statin-mediated reductions in soluble A␤ levels and improvements in cognitive function (15,(35)(36)(37)(38). However, recently statins have been reported to increase the microglial activation in hippocampal slice cultures (39). These results demonstrate the complex were treated with increasing concentrations of simvastatin or lovastatin for 18 h. Cells were lysed, and GTP-loaded Rac was isolated with PAK-GST beads.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, recent prospective studies have demonstrated statin-mediated reductions in soluble A␤ levels and improvements in cognitive function (15,(35)(36)(37)(38). However, recently statins have been reported to increase the microglial activation in hippocampal slice cultures (39). These results demonstrate the complex were treated with increasing concentrations of simvastatin or lovastatin for 18 h. Cells were lysed, and GTP-loaded Rac was isolated with PAK-GST beads.…”
Section: Discussionmentioning
confidence: 74%
“…Using statin-treated hippocampal slice preparations, one study showed that inhibition of protein geranylgeranylation elicited microglial activation (41). Conversely, another study demonstrated that statin-induced inhibition of protein geranylgeranylation suppressed the A␤-stimulated inflammation in microglial cultures (18).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand certain statins have been reported to induce inflammation, for instance lovastatin has been shown to increase IL-1␤ concentration in brain tissue of transgenic mice, which overexpress human amyloid precursor protein (30), and TNF␣ concentration in cultured hippocampal slices (13). Similarly, cerivastatin and fluvastatin have been reported to up-regulate IL-1␤-and IFN␥-induced changes in smooth muscle (31,32) and hepatoma cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…statins) that are distinct from their ability to lower cholesterol. It has been shown that statins reduce A␤ deposition and inflammatory changes in mouse models of Alzheimer disease (12)(13)(14), block paralysis in chronic and relapsing experimental autoimmune encephalomyelitis (15), reduce infarct size in ischemia, and improve neurologic outcome by directly up-regulating brain endothelial nitric-oxide synthase (16). Statins have also been shown to decrease symptoms and mortality in stroke-prone spontaneously hypertensive rats (17).…”
mentioning
confidence: 99%